Dialogue and proclamation of truth: Reception of Nostra aetate and Ad gentes by the FABC - Brazal, Agnes M. (Animo Repository, 2017)
This paper explores the relationship between dialogue and proclamation of Christ in the Vatican II documents Nostra Aetate1 and Ad Gentes2 and their reception by the Federation of Asian Bishops Conference (FABC) – its plenary assembly, as well as the Bishops Institute for Religious Affairs (BIRA) and Formation Institute for Interreligious Affairs (FIRA) seminars under the FABC Office of Ecumenical and Interreligious Affairs.This essay argues that FABC has appropriated as well as gone beyond the teachings of Nostra Aetate and Ad Gentes on dialogue and proclamation. For FABC, the triple dialogue with religions, cultures, and the poor is not just a means but the mode of proclaiming Christ in Asia. Furthermore, unlike Ad Gentes, proclamation of Christ is not aimed at conversion to Christianity, but is, instead, understood as the promotion of God’s reign. In continuity with Nostra Aetate and Ad Gentes, the FABC plenary documents however do not go as far as the BIRA IV and FIRA documents where the discourse on Christianity as fulfilling all the other religions had disappeared.